Pengaruh Sistem Informasi Akuntansi, Pengembangan Sumber Daya Manusia Terhadap Pengendalian Intern dan Laporan Keuangan yang Handal - Mahendra, Denny; Santosa, Jarot; Haryanto, Aris Tri (ITB AAS INDONESIA, 2020)
The Boyolali District Government succeeded in obtaining a Fair Opinion without Exception (WTP) opinion from the Financial Supervisory Agency after conducting an audit of the Boyolali Regency's financial statements in 2016. The Accounting Information System and Human Resource Development System had a significant effect on Internal Control. Accounting Information Systems, Human Resource Development and Internal Control have a significant effect on Reliable Financial Statements. The population of this study is the Regional Work Unit (SKPD) which is responsible for making financial reports in Boyolali Regency, as many as 75 employees. The sampling technique in this study is the census. The results showed that the Accounting Information System has a significant effect on internal control. Human resource development has a significant effect on internal control. Accounting Information Systems have a significant effect on reliable financial statements. Human resource development has a significant effect on reliable financial statements. Internal control has a significant effect on Reliable Financial Statements. The results of the path analysis are known to track the development of human resources on reliable financial statements, which is the dominant or effective path to improving reliable financial statements.